2021
DOI: 10.3390/jof7060432
|View full text |Cite
|
Sign up to set email alerts
|

Citronellal Exerts Its Antifungal Activity by Targeting Ergosterol Biosynthesis in Penicillium digitatum

Abstract: Ergosterol (ERG) is a potential target for the development of antifungal agents against Penicillium digitatum, the pathogen of green mold in citrus fruits. This study examined the mechanism by which citronellal, a typical terpenoid of Cymbopogon nardus essential oil, acts on ergosterol to exhibit its antifungal activity against P. digitatum. We previously reported that citronellal inhibited the growth of P. digitatum with minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) of 1.36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 40 publications
1
30
0
Order By: Relevance
“…The activity of citronellal, the principal constituent (93Á97%) of the essential oil extracted from Eucalyptus citriodora in this study, has already been studied against several fungi, and it has shown interference in membrane integrity and reduction in ergosterol levels as a mechanism of antifungal activity. This substance negatively regulates the ergosterol genes responsible for the conversion of lanosterol to ergosterol (Yang et al 2021). The same mechanisms of antifungal action described above for the chemical constituents of essential oils might have occurred with the fungus Hemileia vastatrix after treatments with Eucalyptus essential oils because these oils also contain these same substances.…”
Section: In Vitro Antifungal Activity Of Essential Oils and Nanoparti...mentioning
confidence: 82%
See 1 more Smart Citation
“…The activity of citronellal, the principal constituent (93Á97%) of the essential oil extracted from Eucalyptus citriodora in this study, has already been studied against several fungi, and it has shown interference in membrane integrity and reduction in ergosterol levels as a mechanism of antifungal activity. This substance negatively regulates the ergosterol genes responsible for the conversion of lanosterol to ergosterol (Yang et al 2021). The same mechanisms of antifungal action described above for the chemical constituents of essential oils might have occurred with the fungus Hemileia vastatrix after treatments with Eucalyptus essential oils because these oils also contain these same substances.…”
Section: In Vitro Antifungal Activity Of Essential Oils and Nanoparti...mentioning
confidence: 82%
“…This substance negatively regulates the ergosterol genes responsible for the conversion of lanosterol to ergosterol (Yang et al . 2021). The same mechanisms of antifungal action described above for the chemical constituents of essential oils might have occurred with the fungus Hemileia vastatrix after treatments with Eucalyptus essential oils because these oils also contain these same substances.…”
Section: Resultsmentioning
confidence: 99%
“…Since cell membrane of fungi in constituents and structures is different from mammalian, using it as a target is attractive for developing selective antifungal agents [47]. Currently, the majority of the available antifungals interfere with its functions either by binding with membrane ergosterol or through inhibition of various steps in ergosterol biosynthesis [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the repressed tendency found in a gene ( ERG2, ERG3, ERG4 ) encoding ergosterol biosynthesis was downregulated by 2.62-, 3.57-, and 2.71-fold, respectively. Previous research reported that ERG3 gene downregulation caused P. digitatum cells to lose the capacity to convert lanosterol to ergosterol ( 61 ).…”
Section: Discussionmentioning
confidence: 99%